A new friend - Lukoff, Kyle; Uno, Kat (2023)
When mermaid Vera and Octo-boy Beaker investigate what seems like a wave of vandalism in Tidal Grove, they discover a baby Mantis shrimp who does not fully understand his own power, and help him find his family.
Ages 4-6.
Grades K-1.
Keywords: Mermaids -- Juvenile fiction; Marine animals -- Juvenile fiction; Friendship -- Juvenile fiction; Mermaids -- Fiction; Marine animals -- Fiction; Friendship -- Fiction; JUVENILE FICTION / Readers / Beginner; JUVENILE FICTION / Mermaids & Mermen; Picture books